What is a feasible and 1.5°C-aligned hydrogen infrastructure for Germany? A multi-criteria economic study based on socio-technical energy scenarios - Franziska Hoffart (RWI - Leibniz-Institut für Wirtschaftsforschung, 2022)
Emission-free hydrogen (H2) is crucial to decarbonize energy supply and to tackle the climate crisis. To unlock the potential of H2, pipelines infrastructures and related investments are required to enable trade. However, it is uncertain what future H2 infrastructure will be needed. The paper aims to assess three H2 infrastructures for Germany within a European context in terms of feasibility (criterion 1) and 1.5°C-alignment (criterion 2) to inform investment and political decisions. Own socio-technical scenarios are used to include findings from four disciplines for a holistic infrastructure evaluation. As results, implementation requirements are identified that determine the future robustness of different supply chains. It is assessed which feasible infrastructures are 1.5°C-aligned in terms of impact for the environment and energy transition, which goes beyond the German context. The results show, that the origin of H2 mainly determines the 1.5°C-alignment and that renewable H2 is more sustainable than fossil-based H2. Also, investments in gas pipelines for future retrofitting might delay energy transitions due to lock-ins and climate-related risks. In conclusion, a step-by-step construction of new H2 pipelines for renewable H2 near industry cluster is advisable. In the light of the chick-and-egg problem of establishing a H2-economy, recommendations on H2 supply and demand are drawn, which are also relevant for an international context.
Keywords: H54; Q42; Q48; O33; 330; Energy transition; socio-technical scenarios; H2 infrastructure; energy policy; climate risks